Tahap Pengurusan Pelajar dan Pengurusan Masa dalam Pengajaran Amali Fizik (Sains Humanika, 2014)
Practical method is a teaching method which uses inquiry-discovery approach; in which a situational problem is given to be solved. The practical approach involves students solving given problems and requires good time management. This working paper seeks to show students’ perception on the level of students’ management and time management in the teaching of practical approach. Six Physics teachers from normal day secondary schools in the Middle Zone were selected through purposive sampling consisting of 3 experienced teachers and 3 novice teachers. A total of 139 questionnaires were answered by students of the concerned teachers. Closed-ended questionnaires were used in this study and data collected were analysed using SPSS. The findings showed the teachers’ level of students’ management and time management in the teaching practical of Physics was good. However, it was found that novice teachers’ level of students’ management was better whereas experienced teachers were better in managing practical time. Results from questionnaire analysis discovered several aspects of students’ management and time management which required emphasis by all Physics teachers. As a conclusion, a few recommendations on students’ management and time management methods in Physics practical were presented to enhance implementation of practical approach by Physics teachers in particular and Science teachers in general.
Keywords: Practical approach; physics teacher; students' management; time management